2024
DOI: 10.1128/mbio.02320-23
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ligase TRIM22 restricts SARS-CoV-2 replication by promoting proteasomal degradation of NSP8

Lujie Fan,
Yuzheng Zhou,
Xiafei Wei
et al.

Abstract: Replication of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) genome is mediated by a complex of non-structural proteins (NSPs), of which NSP7 and NSP8 serve as subunits and play a key role in promoting the activity of RNA-dependent RNA polymerase (RdRp) of NSP12. However, the stability of subunits of the RdRp complex has rarely been reported. Here, we found that NSP8 was degraded by the proteasome in host cells, and identified tripartite motif containing 22 (TRIM22) as its E3 ligase. The interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Another well-characterized antiviral TRIM protein is the E3 ubiquitin ligase TRIM22. TRIM22 restricted IAV and SARS-CoV-2 replication through ubiquitin-proteasome degrading NP and NSP8, respectively ( Di Pietro et al., 2013 ; Fan et al., 2024 ). Rather, TRIM22 suppressed RSV replication by targeting JAK-STAT1/2 signaling ( Wang et al., 2021a ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another well-characterized antiviral TRIM protein is the E3 ubiquitin ligase TRIM22. TRIM22 restricted IAV and SARS-CoV-2 replication through ubiquitin-proteasome degrading NP and NSP8, respectively ( Di Pietro et al., 2013 ; Fan et al., 2024 ). Rather, TRIM22 suppressed RSV replication by targeting JAK-STAT1/2 signaling ( Wang et al., 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that NSP8 was a relatively unstable protein, which could be readily recognized by the E3 ubiquitin ligase TRIM22. TRIM22 was induced upon SARS-CoV-2 infection and mediated Lys48-linked ubiquitination and proteasomal degradation of NSP8 at Lys97 ( Fan et al., 2024 ). TRIM56 has been demonstrated to inhibit various virus replications, such as influenza virus, human coronavirus (HCoV) OC43, yellow fever virus (YFV), and dengue virus serotype 2 (DENV2) ( Liu et al., 2014 ; Liu et al., 2016 ).…”
Section: Coronavirusmentioning
confidence: 99%
See 1 more Smart Citation
“…Some E3 ligases have been identified as anti-coronavirus host factors by inducing viral protein degradation. 26 29 Notably, the Cullin–RING (really interesting new gene) ligases (CRLs) form the largest E3 family, which is evolutionarily conserved and plays crucial roles in many biological processes, including virus infection. 30 33 In humans, the Cullin family comprises eight members: CUL1 (Cullin 1), CUL2, CUL3, CUL4A, CUL4B, CUL5, CUL7, and CUL9.…”
Section: Introductionmentioning
confidence: 99%